Homeoza tiola / disulfida kod pacijenata sa primarnim Sjogrenovim sindromom: Thiol/disulfide homeostasis in pSS - YILMAZ CAKMAK, Nuray; BASER, Salih; ERTEN, Sükran; GEMCIOGLU, Emin; EREL, Ozcan (Journal of Medical Biochemistry, 2020)
ABSTRACT Background/aim Primary Sjögren’s syndrome (pSS) is a disease associated with the overexpression of proinflammatory cytokines, and oxidative stress is one of the factors responsible for its etiopathogenesis. This study aimed to investigate the thiol/disulfide homeostasis in pSS patients. Materials and Methods The study included 68 pSS patients and 69 healthy controls. Thiol/disulfide homeostasis (total thiol, native thiol, and disulfide levels) was measured using the automatic spectrophotometric method developed by Erel and Neselioglu, and the results of the 2 groups were compared. Results The gender and age distributions of the pSS and control groups were similar (P = 1.000 and P = 0.065). Total thiol and native thiol levels were lower in the pSS group than in the control group (470.08 ± 33.65 µmol/L vs. 528.21 ± 44.99 µmol/L, P < 0.001, and 439.14 ± 30.67 µmol/L vs. 497.56 ± 46.70 µmol/L, P < 0.001, respectively). There were no differences in disulfide levels between groups [17.00 (range0.70–217.0) µmol/L vs. 14.95 (range 2.10–40.10) µmol/L, P = 0.195]. Conclusion It was concluded that the thiol/disulfide balance shifted towards disulfide in patients with pSS.